Natural extracts derived from marine sponge-associated bacteria with diverse nonribosomal peptide synthetase genes have anticancer activities - Jepri Agung Priyanto, Widya Esti Purwaningtyas, Dewi Ferantika, Dudi Tohir, Rika Indri Astuti, Aris Tri Wahyudi (Journal of Applied Pharmaceutical Science, 2022)
Marine bacteria carrying nonribosomal peptide synthetase (NRPS) genes could be a promising source of anticancer compounds. This study evaluated the anticancer activity of sponge-associated bacteria with diverse NRPS genes. Nine isolates used in this study possessed diverse NRPS genes, as detected by polymerase chain reaction (PCR) screening. 16S rRNA-based identification exhibited that all nine isolates belonged to the family of Gammaproteobacteria class and were of the genus Pseudoalteromonas, Pseudomonas, or Serratia. Enterobacterial repetitive intergenic consensus- PCR confirmed that all isolates were different strains. Ethyl acetate extracts of the nine bacteria showed toxicity against Artemia salina and median lethal concentration (LC50) values of 30.94–179.41 μg/ml. Of the three bacterial isolates with the lowest LC50, the STIL 37-derived extract showed the highest anticancer activity and a high selectivity index against three cancer cell lines (A549, MCF-7, and WiDr) with median inhibition concentration values of 163.26– 304.51 μg/ml, but there was no effect on human mammary epithelial cells (MCF-12A), as tested by microculture tetrazolium test. According to gas chromatography-mass spectrometry analysis, hexadecanoic acid was found to be the most dominant compound in STIL 37 extract. In conclusion, all nine strains of sponge-associated bacteria, especially STIL 37, could potentially be used in the development of new anticancer drugs.
Keywords: Cytotoxicity, nonribosomal peptide synthetase (NRPS) gene, sponge-associated bacteria, 16S-rRNA